Next Generation Science Standards: veteran high school science teachers’ transfer of learning from formal, nonformal, and informal professional development - Krebs, Anne M. (Kansas State University, 2019)
Twenty states, including Kansas, expect science teachers to utilize the content and learning experiences outlined by the Next Generation Science Standards (NGSS). These standards specify student-centered teaching and learning through inquiry, science and engineering practices, and scientific argumentation. Current science teachers may find it necessary to shift or modify teaching practices to accommodate NGSS expectations. This qualitative multi-case study was designed to explore the experiences of three veteran high school science teachers as they learn about NGSS and transfer NGSS knowledge and teaching strategies to classroom practice. The case study focused on three areas: 1) the participants’ description of NGSS, 2) the influence of the mode of learning delivery — formal professional development, nonformal professional development, and informal learning, and 3) the transfer of NGSS knowledge to teaching practice. Study findings were based on semi-structured interviews, classroom observations, and analysis of documents — professional development notes, class handouts, and grading rubrics. Data were analyzed with a theoretical framework of interpretivism and symbolic interactionism, respecting each participant’s assignment of value and meaning. The conceptual framework incorporated NGSS; learning delivery mode — formal, nonformal, and informal; and transfer of learning to assess participants’ application of learning to teaching practice. A cross-case analysis found that teachers, although they did not utilize NGSS terminology regularly, transferred NGSS knowledge to classroom practice unless the teaching practices conflicted with a pre-existing teaching pedagogy. The study results have implications for professional development staff, school administrators, and science teachers.
Keywords: Adult learning; Next Generation Science Standards (NGSS); Teacher education; Continuing professional education; Science teacher; Professional development (PD)